Mental health consequences of climate change from European perspective - Rýdlo, Ondřej; Boštíková, Vanda (Vojenské zdravotnické listy, 2022)
Society, as much as an individual, has a certain capacity to cope with issues. The preparedness of the society for the issue significantly enhances the ability to overcome the issue with minimum possible harm. This article considers psychological consequences of climate change, the major challenge for society, from the perspective of European security. It proposes an increasement of aggressive behavior and intergroup hostility as a direct and indirect psychological consequence of climate change. In the final section, crisis intervention and de-securitization of climate change debate are considered to serve as mitigating factors for future development.
Keywords: Hostility; Aggression; hodnocení vlivů na zdraví; duševní zdraví; Health Impact Assessment; lidé; nepřátelství; extrémní horko; agrese; Climate Change; Extreme Heat; Mental Health; klimatické změny; Humans